Mathematical literacy in problem-based learning viewed from cognitive styles - Yusfita Yusuf; Mimih Aminah; Yuni Nurfitriani; Kurram Shabbir (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2026)
Abstract The mathematical literacy ability of students in Indonesia remains low. One contributing factor is classroom learning activities that are primarily limited to the transfer of knowledge. Additionally, during the learning process, students with different cognitive styles are suspected to have varying levels of understanding of the same concept. The problem-based learning (PBL) model not only actively involves students but also provides them with opportunities to develop their abilities and foster critical thinking. Hence, this research seeks to explore the interplay between the Project-Based Learning model and cognitive styles in relation to students' mathematical literacy abilities. This quantitative study employed a factorial research design. The subjects comprised 64 junior high school students in Sumedang. Prior to the commencement of the learning process, students completed the Group Embedded Figures Test (GEFT) to identify their cognitive styles. Following this, the experimental class was taught using the Project-Based Learning model, while the control class received conventional instruction over a three-week period. After the learning sessions, students were tested on their mathematical literacy skills. Data analysis was conducted using a two-way ANOVA. The results indicated that an interaction effect was observed between the learning model and cognitive style, influencing students' mathematical literacy skills.